2016
DOI: 10.1155/2016/1748583
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Visual Outcome in Traumatic Cataract Patients

Abstract: Purpose. To investigate the prognostic factors for visual outcome in traumatic cataract patients. Methods. The demographic features of traumatic cataract patients in Central China were studied. The factors that might influence the visual outcome were analyzed. The sensitivity and specificity of OTS (ocular trauma score) in predicting VA were calculated. Results. The study enrolled 480 cases. 65.5% of patients achieved VA at >20/60. The factors associated with the final VA were initial VA, injury type, wound lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
(41 reference statements)
1
8
0
5
Order By: Relevance
“…The mean VA in open globe injury was logMar 1.13±0.9 where as in closed globe injury mean VA was 0.86±0.80. Other studies which had similar results are Ahmad Nadeem Aslami et aland Ying Q et al [12,13]. Brar et al also suggested similar results in pediatric traumatic cataract patients.…”
Section: Original Research Articlesupporting
confidence: 54%
See 2 more Smart Citations
“…The mean VA in open globe injury was logMar 1.13±0.9 where as in closed globe injury mean VA was 0.86±0.80. Other studies which had similar results are Ahmad Nadeem Aslami et aland Ying Q et al [12,13]. Brar et al also suggested similar results in pediatric traumatic cataract patients.…”
Section: Original Research Articlesupporting
confidence: 54%
“…Better initial visual acuity has good final visual outcome. Ying Q et al, Abdul Rahim Aldina et al, Shah et al had similar results on initial visual acuity as predictive factor [13,6,17].…”
Section: Original Research Articlementioning
confidence: 69%
See 1 more Smart Citation
“…In a study by Qi Y et al, (17) it was concluded that 65.5% of patients achieved VA at > 20/60. The factors associated with the final visual outcome were initial VA, injury type, wound location, the way of cataract removal and IOL implantation.…”
Section: Discussionmentioning
confidence: 98%
“…Literatürde travmatik katarakt olgularına GİM implantasyonu oranı %81-94 arasındadır [2,9,13]. Bizim çalışmamızda bu oran %89,4'tür.…”
Section: Gereç Ve Yöntemunclassified